2013
DOI: 10.2147/lctt.s44825
|View full text |Cite
|
Sign up to set email alerts
|

EGFR mutations in patients with lung adenocarcinoma in southwest China: are G719S/A and L861Q more likely detected in tumors derived from smokers?

Abstract: Background:The clinical characteristics of epidermal growth factor receptor (EGFR) hotspot mutations, such as deletions in exon 19, substitution of L858R in exon 21, and mutations in exon 20, have been widely reported in nonsmall cell lung cancer. However, the clinical features of other low frequency EGFR mutations in these four exons (especially the relationship with smoking history), eg, substitutions of G719S/A/C in exon 18 and L861Q in exon 21, remain unclear. This study investigated the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…33 Our data showed that male patients (65%; p <0.05) had higher rate of EGFR uncommon mutations than female patients (35%), which may be partly explained by recent descriptive studies suggesting putative association between uncommon mutations (G719X and L861Q) and smoking history. 34 , 35 Therefore, future studies are needed to clarify definite association between EGFR uncommon mutations and smoking history in Indonesian lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…33 Our data showed that male patients (65%; p <0.05) had higher rate of EGFR uncommon mutations than female patients (35%), which may be partly explained by recent descriptive studies suggesting putative association between uncommon mutations (G719X and L861Q) and smoking history. 34 , 35 Therefore, future studies are needed to clarify definite association between EGFR uncommon mutations and smoking history in Indonesian lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR mutation test was performed on tissue biopsies of all patients using an amplification refractory mutation system (ARMS) with the ADx-ARMS EGFR Mutation Test Kit (Amoy Diagnostics Co., Ltd., Xiamen, China) as previously described. 23 …”
Section: Methodsmentioning
confidence: 99%